The 12-hour shift: radiographers’ perspectives and its applicability during a pandemic - Ooi, J.W.L. (Radiography (Lond), 2021)
INTRODUCTION: Traditionally, shift work for radiographers at our institution comprised of three shift patterns – morning (8am-2pm), afternoon (2pm–9pm) and night (9pm-8am). However, when COVID-19 was first detected in Singapore in January 2020, the 12-h shift was introduced for better team segregation and deployment to meet the service needs of the Emergency Department. The 12-h shift consisted of the day (9am-9pm) and night (9pm-9am) shifts. While the 12-h shift is common to nursing practices, it is new to the radiography profession within the study centre. This study explores the radiographers' perspectives of the new shift and the impact of shift patterns on radiographers' wellness and work performance compared to the original three shift patterns. METHODS: A mixed-methods design study was adopted for this single-centre evaluation. An anonymous online questionnaire was administered to radiographers who had experienced both shift types. Additionally, the number of radiographers who had taken sick leave, and images rejected and accepted from the X-ray consoles were retrospectively collected to measure the impact of the new shift. RESULTS: Radiographers experienced fatigue and appreciated the longer rest days associated with the 12-h shift. Additionally, the sick leave rates and image reject counts were more favourable with the 12-h shift pattern. CONCLUSION: The findings indicate that the extended shift hours are effective during a pandemic but may result in radiographer burnout during a prolonged outbreak. IMPLICATIONS FOR PRACTICE: Studying these variables will provide an effective starting point in understanding the efficacy and applicability of a 12-h shift system during pandemic periods.